Creation of a nationwide breastfeeding policy for surgical residents: a scoping review protocol. Issue 6 (13th June 2022) - Ziolkowski, Natalia; Rogowsky, Larissa; Innis, Julia; Grant Buechner, Angela; Springall, Elena; Dengler, Jana
Abstract : Introduction: Breast feeding is recommended for the first year of a baby's life due to numerous benefits for both the child and mother. After returning from maternity leave, surgical trainees face extensive barriers to breast feeding and tend to terminate breast feeding earlier than guideline recommendations. The aim of this scoping review is to assess existing breastfeeding policies for surgical trainees at the national level including postgraduate medical education offices, provincial resident unions and individual surgical programmes. Methods and analysis: A modified Arksey and O'Malley (2005) framework will be used. Specifically, (1) identifying the research question/s and (2) relevant studies from electronic databases and grey literature, (3) identifying and (4) selecting studies with independent verification, and (5) collating, summarising, and reporting data while having ongoing consultation between experts throughout the process. Experts will include a lactation consultant (AGB), a human resource leader (JI), a health information specialist (ES), two independent coders (NZ, LR) and a board-certified surgeon (JD). This work will take place as of December 2020 and be carried out to completion in 2021. Ethics and dissemination: Ethics approval will not be sought for this scoping review. Research findings will be disseminated through publications, presentations and meetings with relevant stakeholders.